2013 21st International Conference on Geoinformatics 2013
DOI: 10.1109/geoinformatics.2013.6626205
|View full text |Cite
|
Sign up to set email alerts
|

Exploring carbon emissions, economic growth, energy and R&D investment in China by ARDL approach

Abstract: This paper examines the causal relationship among economic growth, energy structure, R&D investment and carbon emission in China by using autoregressive distributed lag bounds testing approach of cointegration during the period of 1990 -2011. In order to examine this linkage, theauthors use the two-step procedures. Firstly, theauthors conducted the unit root tests to measure whether the single integrated of time series is not more than 1. Secondly, theauthors explore the long-run relationships between the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this case our paper does not support the current literature of EKC in BRICS countries. In fact, as described in the literature review, some authors (Honglei et al, 2011;Xuemei et al, 2011;Zhai and Song, 2013) found a simultaneous increase in economic parameters and a decrease in pollution in China. According to these studies, China was positioned in the second half of the curve, the section with a negative inclination and not in the first half as according to our results.…”
Section: Figure 1 Environmental Kuznets Curvementioning
confidence: 90%
See 1 more Smart Citation
“…In this case our paper does not support the current literature of EKC in BRICS countries. In fact, as described in the literature review, some authors (Honglei et al, 2011;Xuemei et al, 2011;Zhai and Song, 2013) found a simultaneous increase in economic parameters and a decrease in pollution in China. According to these studies, China was positioned in the second half of the curve, the section with a negative inclination and not in the first half as according to our results.…”
Section: Figure 1 Environmental Kuznets Curvementioning
confidence: 90%
“…Other studies have not found a positive relationship between GDP and improved environmental quality. Zhai and Song (2013) investigated the causal relationship in China between economic growth, energy structure, R&D investments, and carbon emissions. They found that the impact of economic growth and R&D investments on carbon emissions was insignificant both in the long and short term.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This implies that, although advanced technologies might improve resource-use efficiency, their economic scale also quickly grows, demanding more natural resource inputs, resulting in higher CO 2 emissions (Cheng et al, 2019). (Zhai & Song, 2013) discover that R&D had no discernible influence on China's long-and shortterm CO 2 emissions. According to (Cheng et al, 2019), technological innovations had a negligible effect on CO 2 emissions in OECD countries, but the effects were positive in countries with moderate CO 2 emission levels.…”
Section: Research and Development And Co 2 Emissionsmentioning
confidence: 99%
“…Sim [27] studied the economic and environmental value of renewable energy investments, with the conclusion that the government should increase renewable energy subsidies and investment, and should also reevaluate its R&D investment strategy to reduce carbon emissions. Zhai and Song [28] also conducted a similar study on China and found that there is no causal relationship between the impact of economic growth and investment in renewable energy on carbon emissions, regardless of the short-term or long-term relationship. However, the reduction of carbon emissions caused by the development of renewable energy has a negative impact on the economy.…”
Section: Introductionmentioning
confidence: 99%